Weaving Pluralism in Character Education Based on Bugis Local Wisdom at IAIN Palopo - Yunus (JURNAL PENELITIAN, 2025)
Strengthening local wisdom is important in character education to foster empathetic and tolerant attitudes in a multicultural society. This research aims to examine the values of Bugis local wisdom and their application in character education. A qualitative approach employing content analysis was used to analyze literature and field data in order to identify the core values of Bugis local wisdom. The findings reveal that Bugis local wisdom aligns with the values of pluralism in Indonesia, as reflected in the concept of pesse (empathy). This concept is manifested through principles such as Sipakatau (humanizing others), Sipakalebbi (mutual respect), Sipakainge (mutual reminding), and Sipakatou (mutual recognition). Bugis proverbs, including “Mali siparappe, rebba sipatokkong, malilu sipakainge,” further illustrate the spirit of mutual cooperation and social concern. At IAIN Palopo, these values were implemented through the tudassipulung and Living Values models and were found to be effective in developing key character traits among students, including empathy, compassion, togetherness, respect for differences, willingness to sacrifice, tolerance, and mutual assistance. These behaviors were observed both inside and outside the classroom, indicating that character education grounded in Bugis local wisdom effectively shapes student behavior in accordance with the culture’s noble values.